2014
DOI: 10.3892/ijo.2014.2292
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of the T-box transcription factor Brachyury increases sensitivity of adenoid cystic carcinoma cells to chemotherapy and radiation in vitro: Implications for a new therapeutic principle

Abstract: Adenoid cystic carcinoma (AdCC) is highly metastatic and resistant to chemotherapy and radiotherapy. Recently, we reported that the T-box transcription factor Brachyury is a potential regulator of cancer stem cells (CSCs). Specifically, growth of CSCs was found to be controlled by Brachyury knockdown in AdCC. Since CSCs are resistant to chemotherapy and radiotherapy, this finding provides a new principle for therapies targeting CSCs. In the present study, we established that Brachyury knockdown suppresses chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 44 publications
(49 reference statements)
2
19
0
Order By: Relevance
“…These results are consistent with those of previous studies, which revealed that silencing brachyury expression inhibits tumor formation and metastasis in human adenoid cystic carcinoma cells (19,20). In addition, a previous study revealed that brachyury expression is associated with EMT and lymph node metastasis in OSCC patients (22).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results are consistent with those of previous studies, which revealed that silencing brachyury expression inhibits tumor formation and metastasis in human adenoid cystic carcinoma cells (19,20). In addition, a previous study revealed that brachyury expression is associated with EMT and lymph node metastasis in OSCC patients (22).…”
Section: Discussionsupporting
confidence: 82%
“…However, the role of these genes in CSCs remains unclear. Recently, the T-box transcription factor brachyury, which is essential for mesoderm formation during early development (16,17), has been found to regulate the epithelial-mesenchymal transition (EMT) and CSC potential in human salivary carcinoma cells (18)(19)(20)(21). In addition, brachyury expression was found to correlate with lymph node metastasis in OSCC (22).…”
Section: Introductionmentioning
confidence: 99%
“…Post-developmentally, brachyury is expressed in the testes and some thyroid tissues, but is undetectable in all other non-neoplastic adult tissues (Edwards et al, 1996; Hamilton et al, 2015). Interestingly, recent studies have reported the expression of brachyury in several epithelial cancers where it promotes growth, confers resistance to chemo- and radiotherapy, and drives epithelial-to-mesenchymal transition (EMT) (Cho et al, 2010; Fernando et al, 2010; Haro et al, 2013; Huang et al, 2013; Imajyo et al, 2012; Jezkova et al, 2016; Kobayashi et al, 2014; Larocca et al, 2013; Li et al, 2016; Miettinen et al, 2015; Palena et al, 2014; Park et al, 2008; Pinto et al, 2015; Pinto et al, 2014; Pires and Aaronson, 2014; Roselli et al, 2012; Sarkar et al, 2012; Shao et al, 2015; Shimoda et al, 2012; Vujovic et al, 2006; Xu et al, 2015; Yoshihama et al, 2016); however, the mechanistic details of how brachyury mediates these features of tumor progression have not been fully elucidated. Furthermore, the lack of brachyury expression in most adult non-neoplastic tissues and exclusive tumor-specific expression underscores its value as a potential diagnostic and therapeutic target in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…For the experimental metastasis studies, 1×10 6 cells in 40 μl PBS were injected into the tongue of mice under intraperitoneal diethyl ether anesthesia, using a syringe with a 27gauge disposable needle (TOP Plastic Syringe, Tokyo, Japan). The primary tumor volumes were measured weekly, calculated as length × width × thickness, and the mice were sacrificed when the primary tumor volume reached 100 mm 3 . After sacrifice, the tongue, cervical lymph nodes, lungs, and liver were observed macroscopically.…”
Section: Methodsmentioning
confidence: 99%